Human monocyte-derived suppressive cells (HuMoSC) for cell therapy in giant cell arteritis - Samson, Maxime; Genet, Coraline; Corbera-Bellalta, Marc; Greigert, Hélène; Espígol-Frigolé, Georgina; Gérard, Claire; Cladière, Claudie; Alba-Rovira, Roser; Ciudad, Marion; Gabrielle, Pierre-Henry; Creuzot-Garcher, Catherine; Tarris, Georges; et al. (Frontiers in Immunology, 2023)
The pathogenesis of Giant Cell Arteritis (GCA) relies on vascular inflammation and vascular remodeling, the latter being poorly controlled by current treatments. This study aimed to evaluate the effect of a novel cell therapy, Human Monocyte-derived Suppressor Cells (HuMoSC), on inflammation and vascular remodeling to improve GCA treatment. Fragments of temporal arteries (TAs) from GCA patients were cultured alone or in the presence of HuMoSCs or their supernatant. After five days, mRNA expression was measured in the TAs and proteins were measured in culture supernatant. The proliferation and migration capacity of vascular smooth muscle cells (VSMCs) were also analyzed with or without HuMoSC supernatant. Transcripts of genes implicated in vascular inflammation (CCL2, CCR2, CXCR3, HLADR), vascular remodeling (PDGF, PDGFR), angiogenesis (VEGF) and extracellular matrix composition (COL1A1, COL3A1 and FN1) were decreased in arteries treated with HuMoSCs or their supernatant. Likewise, concentrations of collagen-1 and VEGF were lower in the supernatants of TAs cultivated with HuMoSCs. In the presence of PDGF, the proliferation and migration of VSMCs were both decreased after treatment with HuMoSC supernatant. Study of the PDGF pathway suggests that HuMoSCs act through inhibition of mTOR activity. Finally, we show that HuMoSCs could be recruited in the arterial wall through the implication of CCR5 and its ligands. Altogether, our results suggest that HuMoSCs or their supernatant could be useful to decrease vascular inflammation and remodeling in GCA, the latter being an unmet need in GCA treatment.